Effectiveness of Various Mosquito Attractant Solutions to Control Mosquito Population - Faridah, Lia; Albert, Christian; Fauziah, Nisa (Universitas Islam Bandung, 2019)
The vector-borne disease is a disease caused by an organism that can transmit disease between human or animal to human. In Indonesia, several vector-borne diseases are a burden of the government including dengue fever, chikungunya, filariasis, and malaria. The attractive baited lethal ovitrap (ALOT) is a novel strategy to alleviate mosquito populations in three main actions: attraction, an adulticide, and larvacide. Research using plant infusion can attract mosquitoes to lay their eggs is needed. This study aims to compare the effectiveness of the mosquito repellent solution using materials from organic waste in Bandung. This study was a quantitative analytic study with a quasi-experimental design conducted in the Faculty of Medicine Universitas Padjadjaran area in October 2016–July 2017. Research subjects are mosquito eggs in a solution which placed at 25 different places for every solution. The analysis was performed using Kruskal-Wallis test followed by the Dunn test. The result of the Kruskal-Wallis test indicates the difference of effectiveness of each solution (p<0.05). Based on the results of the Dunn test, the most significant difference found in the solution of wood shavings with the vegetable waste solution and the solution of wood shavings with corn straw (p<0.05). In conclusion, there is a difference in the effectiveness of the mosquito repellent solutions and the most attractive solution for mosquitoes to oviposit is the corn straw solution. EFEKTIVITAS BERBAGAI LARUTAN PENARIK NYAMUK UNTUK MENGONTROL POPULASI NYAMUKPenyakit tular vektor adalah penyakit yang disebabkan oleh organisme yang dapat mentransmisikan penyakit antarmanusia atau hewan ke manusia. Di Indonesia, terdapat beberapa penyakit tular vektor yang masih menjadi beban pemerintah, di antaranya demam berdarah, chikungunya, penyakit kaki gajah, dan malaria. Attractive baited lethal ovitrap (ALOT) merupakan strategi baru untuk menurunkan populasi nyamuk dalam tiga aksi utama, yaitu attraction, adulticide, dan larvacide. Penelitian terkait larutan dari tanaman yang dapat menarik nyamuk sangat diperlukan. Penelitian ini bertujuan membandingkan efektivitas larutan penarik nyamuk dengan menggunakan bahan dari limbah organik yang ada di Kota Bandung. Penelitian ini adalah penelitian analitik kuantitatif dengan desain quasi-eksperimental yang dilakukan di lingkungan Fakultas Kedokteran Universitas Padjadjaran pada bulan Oktober 2016–Juli 2017. Subjek penelitian merupakan telur nyamuk yang ada pada larutan yang diletakkan pada 25 titik untuk setiap larutan. Analisis dengan Uji Kruskal-Wallis yang dilanjutkan dengan Uji Dunn. Hasil penelitian dengan Uji Kruskal-Wallis menunjukkan perbedaan efektivitas tiap-tiap larutan (p<0,05). Berdasar atas hasil Uji Dunn, perbedaan yang paling signifikan terdapat pada larutan serutan kayu dengan larutan sampah sayur dan larutan serutan kayu dengan jerami jagung (p<0,05). Simpulan, terdapat perbedaan efektivitas larutan penarik nyamuk dan larutan yang menarik nyamuk paling banyak untuk bertelur adalah larutan jerami jagung.